5-Keto-3-cyano-2, 4-diaminothiophenes as selective maternal embryonic leucine zipper kinase inhibitors. Issue 4 (15th February 2019) - Boutard, Nicolas; Sabiniarz, Aleksandra; Czerwińska, Klaudia; Jarosz, Małgorzata; Cierpich, Anna; Kolasińska, Ewa; Wiklik, Katarzyna; Gluza, Karolina; Commandeur, Claude; Buda, Anna; Stasiowska, Agata; Bobowska, Aneta; et al.
Graphical abstract: Abstract: Maternal embryonic leucine zipper kinase (MELK) is involved in several key cellular processes and displays increased levels of expression in numerous cancer classes (colon, breast, brain, ovary, prostate and lung). Although no selective MELK inhibitors have yet been approved, increasing evidence suggest that inhibition of MELK would constitute a promising approach for cancer therapy. A weak high-throughput screening hit (17, IC50  ≈ 5 μM) with lead-like properties was optimized for MELK inhibition. The early identification of a plausible binding mode by molecular modeling offered guidance in the choice of modifications towards compound52 which displayed a 98 nM IC50 . A good selectivity profile was achieved for a representative member of the series (29 ) in a 486 protein kinase panel. Future elaboration of52 has the potential to deliver compounds for further development with chemotherapeutic aims.